Outbreak of Ichthyophthirius multifiliis associated with Aeromonas hydrophila in Pangasianodon hypophthalmus: The role of turmeric oil in enhancing immunity and inducing resistance against co-infection - Kumar, V.; Das, B. K.; Swain, H. S.; Chowdhury, H.; Roy, S.; Bera, A. K.; Das, R.; Parida, S. N.; Dhar, S.; Jana, A. K.; Behera, B. K. (Frontiers in Immunology, 2022)
Ichthyophthirius multifiliis, a ciliated parasite causing ichthyophthiriasis (white spot disease) in freshwater fishes, results in significant economic loss to the aquaculture sector. One of the important predisposing factor for ichthyophthiriasis is low water temperature (i.e. below 20 °C), which affects the health and make freshwater fishes more susceptible to parasitic infections. During ichthyophthiriasis, fishes are stressed and acute immune reactions compromised, which enables the aquatic bacterial pathogens to simultaneously infect the host and increase the severity of disease. In the present work, we aimed to understand the parasite-bacteria co-infections mechanism in fish. Later, Curcuma longa (turmeric) essential oil was used as promising management strategies to improve immunity and control co-infections in fish. A natural outbreak of I. multifiliis was reported (validated by 16S rRNA PCR and sequencing method) in Pangasianodon hypophthalmus from a culture facility of ICAR-CIFRI, India. The fish showed clinical signs including hemorrhage, ulcer, discoloration, and redness in the body surfaces. Further microbiological analysis revealed that Aeromonas hydrophila was associated (validated by 16S rRNA PCR and sequencing method) with the infection and mortality of P. hypophthalmus, confirmed by haemolysin and survival assay. This created a scenario of co-infections, where both infectious agents are active together and causing ichthyophthiriasis and motile aeromonas septicaemia (MAS) in P. hypophthalmus. Interestingly, turmeric oil supplementation induced protective immunity in P. hypophthalmus against the co-infection condition. The study showed that P. hypophthalmus fingerlings supplemented with turmeric oil, at an optimum concentration (10 ppm), exhibited significantly increased survival against co-infection. The optimum concentration induced anti-stress and antioxdative response in fingerlings, marked by significant decrease in cortisol and elevated levels of superoxide dismutase (SOD) and catalase (CAT) in treated animals as compared with the controls. Furthermore, the study indicated that supplementation of turmeric oil increases both non-specific and specific immune response and significantly higher values of HSP70, HSP90 and IgM were observed in P. hypophthalmus treatment groups. Our findings suggest that C. longa (turmeric) oil modulates stress, antioxidant and immunological responses, probably contributing to enhanced protection in P. hypophthalmus.